PERLADANGAN WILAYAH GARIS DEPAN Studi diversifikasi ekonomi di kalangan komunitas peladang - , MUHAMMAD ICHSAN R, Dr. Pujo Semedi H.Y., M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kihambatang is a village located in the heart of tropical rainforest Kalimantan. Geographically tis village located at Schwanner â Muller range. Villagers in Kihambatang are dependent to natural or forest resources around them, which is proven by the swidden agriculture practices among them. One of the most significance mode of production there as in other region in Kalimantan is swidden agriculture or shifting cultivation. The problem is that that/the modeof production is always changing depends on condition in time and place. there are 2 factors which caused those changes. On the other hand, the forest and environment also havesocial meanings for the villagers aside of as natural resources.Because of that, problems arose when they build new relations with new actors around their village. New actors or outsiders who came to Kalimantan have established and controlled the market since first century A.D. It was started by Chinese and continued to British and Dutch Collonialists , up to the logging companies and NGOs in the present time. Most of them see Kalimantan as an island that gives benefit to them by extracting the natural or social resources. For them Kalimantan isseen as a frontier land. In that context, there was a dynamics in swidden agriculture and it also has had impact to it like diversification and access differentiation. This paper discuss the impact of the swidden agriculture diversification process to villagers access to the natural resources, and how the process of swidden agriculture dynamics in Kihambatang takes shape. This paper made by two months research in Kihambatang village, subdistrict of Katingan Hulu, Katingan district, Central Kalimantan. The research method is participation observation, depth â open interview, visual documentation (photo and video) to make a qualitatifdata. Seeing the dynamics by using historical context and also made a aggreation in order tomake a significant correlation.